Characterization of Drayage Activities in the Paso Del Norte Airshed. Issue 9 (September 2019) - Jaikumar, Rohit; Farzaneh, Reza; Ramani, Tara; Johnson, Jeremy
The overall objective of the study was to characterize drayage truck activity and associated emissions in the Paso del Norte region, which is the binational region covering El Paso in Texas and Ciudad Juárez in Mexico. Drayage trucks are a significant source of emissions in the Paso del Norte airshed. The region faces air quality problems and characterizing the unique operational and emission characteristics of drayage vehicles can better support regional air quality planning. In this study, the global positioning system and portable activity measurement system units were fitted to a sample of drayage trucks operating in the El Paso region. The resulting data were analyzed to generate trip-level information on truck activity, along with key parameters, such as speeds, origin, destination, and length. The individual trip information was also used to identify key freight corridors and to estimate emissions associated with drayage activity. The study dataset showed that the Ysleta-Zaragoza International Bridge is the most utilized by the trucks. The facilities visited in the United States tended to be more clustered closer to this bridge, in less urbanized areas, while facilities visited in Mexico tended to be more spread out geographically. Corridor truck volumes and emissions were plotted on maps to visualize emission impacts of drayage trucks, with urbanized areas and areas close to border bridges likely most affected because of higher volumes and emissions. The findings from the study provide an understanding of air quality impacts of drayage trucks in the Paso del Norte airshed.